Thermomagnesium as a fertilizer for soybean: carbohydrate metabolism, silicon–magnesium fertilizer, and grain yield - Moretti, Luiz Gustavo [UNESP]; Crusciol, Carlos Alexandre Costa [UNESP]; Bossolani, João William [UNESP]; Garcia, Ariani [UNESP]; Rossi, Ricardo [UNESP]; Moreira, Adônis (Taylor & Francis, 2021)
Thermomagnesium (TM) or magnesium (Mg) silicate (MgSiO3) is a byproduct of the nickel (Ni) industry. As a fertilizer, TM elevates the pH of acidic soils as well as provides Mg and silicon (Si) to plants. This novel practice can be a pivotal sustainable strategy to enhance soybean [Glycine max (L.) Merrill] development, particularly in tropical environments. Therefore, the present study aimed to evaluate the effects of TM application on the chemical properties of soil; Mg and Si contents in soil and plants; contents of reducing sugars, sucrose, and starch in leaves; and yield of soybean. The experiment was performed under controlled conditions in a greenhouse during the 2016–2017 cropping season. Two soil types (clayey and sandy) and five TM rates (0, 55, 273, 709, and 2,018 mg kg−1 of TM, and 0, 293, 410, 645, and 1,260 mg kg−1 of TM, respectively) with four replicates were used. In both soil types, pH as well as Mg and Si contents increased with increasing TM rates. Similarly, leaf contents of Mg, Si, reducing sugars, and sucrose as well as yield of soybean increased with increasing TM rates. Conversely, leaf starch content decreased with increasing TM rates. Therefore, TM positively affects whole-plant carbohydrate partitioning, thereby improving soybean development, grain filling, and yield.
Keywords: Beneficial element; carbohydrate partitioning; Glycine max; nickel slag; remineralizer